Power, accountability, and humanism [review of] - Pacho, Arturo G. (Philippine Journal of Public Administration, 1980)
A review of Jerome B. McKinney and Lawrence C. Howard, Public Administration: Balancing Power and Accountability (Oak Park, Illinois: Moore Publishing Co., 1979), 436 pp.; Robert S. Lorch, Public Administration (St. Paul Minnesota: West Publishing Co., 1978), 314 pp.; Fred A. Krarnmer, Dynamics of Public Bureaucracy: An Introduction to Public Administration (Cambridge, Massachusetts: Winthrop Publishers, Inc., 1977), 290 pp., and Howard E. McCurdy, Public Administration: A Synthesis (Menlo Park, California: Cummings Publishing Co., 1977), 424 pp.